Why alone? Sensing children's social interactions in the playground - Ferreira, Maria José; Caraban, Ana; Lyra, Olga; Belim, Vítor; Karapanos, Evangelos (My University, 2015)
Inclusive education, or the idea of 'one school for all' has received wide interest in recent years, yet researchers have criticised a lack of empirical evidence on how exclusion is manifested in pupils' behaviours. This paper presents Proximy, a mobile app that senses children's social interactions during free play through sampling the Bluetooth signal strength (RSSI) of nearby devices. We present the design of Proximy and our preliminary social network analysis from a 3-week deployment with 137 seven-to-ten year old students.
Keywords: Inclusive education; Mobile sensing; Social sensing